THE INFLUENCE OF QUALITY OF SERVICE, COMMITMENT AND QUALITY OF ACCOUNTING INFORMATION SYSTEMS ON COMMUNITY SATISFACTION (Survey in Kalikotes District, Klaten Regency) - Dinar Irfani Sodiq; Hadi Samanto; Sri Laksmi Pardanawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research entitled "The Influence of Service Quality, Commitment and Quality of Accounting Information Systems on Community Satisfaction". The purpose of this research is to analyze the effect of service quality on community satisfaction, the effect of commitment on community satisfaction and the influence of the quality of accounting information systems on community satisfaction. This research design is quantitative. The population in this research is the community of Kalikotes sub-district, Klaten district. The sample in this research was 100 respondents. The collecting data in this research using a questionnaire. The test instrument was analyzed using descriptive tests, validity and reliability tests. Classical assumption test was analyzed using normality test, multicollinearity test, heteroscedasticity test. The analytical method used in this research is multiple linear regression analysis, F test, t test and test of determination (R2). The results of the analysis of this research are Service Quality, Commitment and Quality of Accounting Information Systems has a simultaneous effect on community satisfaction in Kalikotes sub-district, Klaten Keywords: Quality of Service, Commitment, Quality of Accounting Information Systems and Community Satisfaction